Is mannan-binding lectin (MBL) detectable on monocytes and monocyte-derived immature dendritic cells?. (19th November 2008) - MacDonald, Shirley L.; Downing, Ian; Turner, Marc; Kilpatrick, David C.
Abstract : MBL (mannan-binding lectin; also called mannose-binding lectin) is a circulating C-type lectin with a collagen-like region synthesized mainly by the liver. MBL may influence susceptibility to infection in recipients of stem cell transplants, and it has even been suggested that the MBL status of a donor can influence the recipient's susceptibility to post-transplant infections. We have previously reported that MBL can be detected on human monocytes and monocyte-derived dendritic cells, based on detection using biotinylated anti-MBL, suggesting that those cells could synthesize MBL. If true, permanent MBL replacement therapy could be achieved by stem cell infusions. However, two other groups independently failed to find mbl - 2 -derived mRNA in monocytes. Therefore, to confirm or refute our previous observations, we used an alternative experimental strategy. Instead of using biotinylated antibody and labelled streptavidin, detection of surface MBL was attempted using MBL-specific primary antibodies (131-1, 131-10 and 131-11) followed by fluorescein-labelled anti-IgG, and controlled by the use of non-specific IgG as primary antibody. Monocytes were counterstained with anti-CD14-PE before FACS analysis. Adherent monocytes were also cultured for 48 h in serum-free medium or converted into immature dendritic cells by culture with IL-4 (interleukin-4) and GM-CSF (granulocyte/monocyte colony-stimulating factor). During FACS analysis, the dendritic cells were gated after counter-staining with anti-CD1a-PE. MBL was readily detected on the surface of fresh monocytes using all three specific anti-MBL monoclonal antibodies, but specific anti-MBL binding was greatly diminished after monocytes had been cultured for 2 days in serum-free medium. Moreover, we could not detect any MBL present on the surface of monocyte-derived dendritic cells. We therefore conclude that MBL is indeed present on the surface of fresh human monocytes. However, in view of the mRNA findings of others and our own previous observation that no secretion of MBL took place in culture, we presume that the surface-bound MBL is derived from autologous plasma and not synthesized by the cells. This conclusion is consistent with our in vivo findings in stem cell transplant patients which provided evidence against significant extra-hepatic production of serum MBL. It provides no ready explanation for the remarkable observation of Mullighan, Heatley, Doherty, Szabo, Grigg, Hughes, Schwarer, Szer, Tait, Bik To and Bardy [(2002) Blood 99, 3524–3529] that the presence of variant alleles of mbl - 2 in stem cell donors can influence susceptibility to serious infections in their recipients.